Réponses

2013-08-02T15:55:16+02:00

A)   8x − (7 + 2x)  =  3(3x − 4)

          8x − 7 − 2x  =  9x − 12

                   6x − 7  =  9x − 12

                 6x − 9x  =  −12 + 7

                       −3x  =  −5

                            x  =  −5/−3

                            x  =  5/3

 

 

 

B)   (9/4x − 3) (4x + 5)  =  0

  

       Comme un produit de facteurs est nul si l'un des facteurs est nul, on a deux solutions :

       —  soit   9/4x − 3  =  0       ⇔     x  =  3 × 4/9  =  4/3

       —  soit      4x + 5  =  0       ⇔     x  =  −5/4

 

 

 

C)        x + 2/5  =  4 − x/6 + x − 2/30

      x + x/6 − x  =  4 − 2/30 − 2/5

                  x/6  =  120/30 − 2/30 − 12/30

                  x/6  =  106/30

                     x  =  106/5